Astrophysical consequences of cold dark matter - N. Riazi (Iranian Journal of Physics Research, 2002)
There are several observational evidences for the existence of dark matter in the universe. More than about 90% of the matter in the universe is in a form which is not directly observable. If the dark matter is in the form of weakly interacting massive particles (WIMPs) or cosmions, part of it is captured by the Sun, other stars, and even planets. In this paper, some basic ideas of the cosmion hypothesis are presented and the abundance and the coefficient of thermal energy transport by WIMPs are calculated, using an approximate method.